2018
DOI: 10.1098/rspb.2018.2120
|View full text |Cite
|
Sign up to set email alerts
|

Prey abundance and urbanization influence the establishment of avian predators in a metropolitan landscape

Abstract: Urbanization causes the simplification of natural habitats, resulting in animal communities dominated by exotic species with few top predators. In recent years, however, many predators such as hawks, and in the US coyotes and cougars, have become increasingly common in urban environments. Hawks in the Accipiter genus, especially, are recovering from widespread population declines and are increasingly common in urbanizing landscapes. Our goal was to identify factors that determine the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 55 publications
2
29
0
1
Order By: Relevance
“…This result is in agreement with studies from the United-Kingdom suggesting that the increase in Sparrowhawks in urban areas might be involved in the decline of local House Sparrow populations (Bell et al 2010). The Eurasian Sparrowhawk is indeed a major predator of House Sparrows (Anderson 2006;Bell et al 2010), especially near urban areas (Tinbergen 1946;Opdam 1979;Frimer 1989;Gotmark and Post 1996;Solonen 1997;Millon et al 2009;McCabe et al 2018). By preferentially predating on House Sparrows, Sparrowhawks are likely to have a direct negative effect on House Sparrow populations.…”
Section: Dependent Variablesupporting
confidence: 88%
See 1 more Smart Citation
“…This result is in agreement with studies from the United-Kingdom suggesting that the increase in Sparrowhawks in urban areas might be involved in the decline of local House Sparrow populations (Bell et al 2010). The Eurasian Sparrowhawk is indeed a major predator of House Sparrows (Anderson 2006;Bell et al 2010), especially near urban areas (Tinbergen 1946;Opdam 1979;Frimer 1989;Gotmark and Post 1996;Solonen 1997;Millon et al 2009;McCabe et al 2018). By preferentially predating on House Sparrows, Sparrowhawks are likely to have a direct negative effect on House Sparrow populations.…”
Section: Dependent Variablesupporting
confidence: 88%
“…Several hypotheses have been suggested to explain the recent decline of House Sparrows. Among them, increasing inter-specific competition (Summers-Smith 2003, increasing predation rates (Eurasian Sparrowhawk, Accipiter nisus, Bell et al 2010;McCabe et al 2018), or the spread of diseases across species (Hartup et al 2001) may contribute to the observed decline. Moreover, this decline could also be linked to the emergence or intensification of pollution sources specific to cities: noise pollution (Meillère et al 2015a, b), light pollution (Dominoni et al 2013), air pollution Lehikoinen 1995, 1996;Llacuna et al 1996;Eeva et al 2009), or even electromagnetic radiations (Balmori and Hallberg 2007;Balmori 2009;Singh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fewer prey species in cities promotes higher population densities for those species that can exploit the urban environment (Steinberg et al, 1997;Uno et al, 2010). Such surges in prey population densities can in turn drive predator population increases, potentially fueling human-wildlife conflict (Yirga et al, 2017;Fleming, & Bateman, 2018;Mccabe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Abundant prey species associated with urban environments such as brown rats (Rattus norvegicus), rock pigeons (Columba livia), and house mice (Mus musculus) could potentially be driving predation rates and protein (i.e. nitrogen) consumption, at least for mammalian and avian predators (Corsini et al;Newsome et al, 2010;Mccabe et al, 2018;Scholz et al, 2020). Our findings are contrary to an emerging hypothesis of relaxed predation phenomenon in urban areas, described by a meta-analysis of 25 studies that found predation rates on bird nests were reduced in urban areas (Eötvös et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation